Hubungan Antara Reward dan Kinerja Karyawan di X Kopi dan Eatery di Yogyakarta - Febrio Valentino; Muslimah Zahro Romas; Dewi Handayani Harahap (Jurnal Psikologi, 2022)
This research was airned to know the correlation between reward and employee work performance. Participants of this research were 47 employees from a cafe in Yogyakarta Method of research is quantitative with population reseach. Data collection tool is using Reward Scale and Work Performance Scale. Method of data analysis in this study is using a product moment correlation analysis techniques.The results showed a correlation value of rxy = 0,750 with a significance level of p = 0,000 (p <0.01). Value of R² = 0,562. This means that the effective amount of donations given reward variable in increasing employee work performance variables of 56.2%. It is about 78.72% (37 respondents) of subjects have high work performance. The results show that there is a very significant positive correlation between reward and employee work performance. The more they received reward, the higher their work performance becomes.